SALBUTAMOL AMELIORATES THE PHENOTYPE OF THE SKIN INFLAMMATORY DISEASE PSORIASIS ACCORDING TO SKIN SPHEROID MODELS - Somuncu, Ozge Sezin; Demiriz, Berke; Turkmen, Irem; SOMUNCU, SALİH; SOMUNCU, SALİH; AKSOY, BERNA (My University, 2021)
Psoriasis is a multifactorial chronic inflammatory disorder resulting by the interplay of genetics, the immune system and the environment. It is characterized by the hyperproliferation of epithelial cells, generating red, itchy psoriatic plaques which have no cure but have great negative impact in patients- life. Although corticosteroids or vitamin D analogs might help recovery to some extent, there is yet no total cure for the disease. In this study, we sought to generate three-dimensional (3D) stress-related psoriatic skin spheroids with the screening of the potential efficacy of a beta(2)-adrenergic receptor agonist, salbutamol. 3D Culture spheroids with human dermal fibroblasts (HDF), human epithelial keratinocytes (HEK) and human monocytic cell line (THP-1) were generated as a representative model of skin and the protocol of stress-related modelling was conducted. The efficacy of the drug salbutamol was evaluated by the changes in mRNA and protein expression levels of selected genes, as well as by several metabolic assays. We developed a method for culturing spherical organoid models of psoriasis in vitro. We tested the potential theurapetic effects of salbutamol on psoriasis spheroids. Spheroids treated with salbutamol indicated the effictiveness of the treatment. 3D spheroid system was found partially efficient for mimicking the physiological features of psoriasis in vitro. This present work may be a starting point for future investigation as it is the first to generate a stress-related psoriatic model and first to try a beta(2) agonist as a potential treatment option. Considering the effects and suitability of topical application of salbutamol, its efficacy should not be underestimated and should be investigated further for translating this knowledge into clinics.